Aspects of transthoracic echocardiography protocol in obese patients - O. N. Dzhioeva; O. A. Maksimova; E. A. Rogozhkina; O. M. Drapkina (Российский кардиологический журнал)
Often, transthoracic echocardiography in obese patients reveals normal indicators of intracardiac hemodynamics and heart geometry. Can the clinician determine the risk of cardiovascular events and proper management in such patients based on the data obtained? Do many overweight patients really have no cardiac abnormalities, or they simply could not be detected? New capabilities of transthoracic echocardiography make it possible to detect abnormalities in the early stages of the disease, even in the absence of clinical manifestations. Thus, the inclusion of additional parameters in the standard protocol of echocardiography in obese patients will most accurately determine the management tactics and prognosis, thereby reducing the risk of unfavorable outcomes.